Gender Equality In Early Childhood Education: A Literature Review Of Global Practices and Challenges - Andi Al Muhammad Ardiansyah; Saqjuddin Saqjuddin (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
Gender equality in Early Childhood Education (ECE) is a fundamental aspect of building an inclusive and just society from the earliest stages of life. This literature review aims to examine global practices and challenges related to gender equality in ECE, with a particular focus on how gender stereotypes are formed and reinforced in early learning environments. Using a systematic literature review (SLR) approach, this study analyzes 25 recent peer-reviewed articles and policy documents published between 2019 and 2024, sourced from reputable academic databases and institutional reports. The findings reveal that gender bias is often reproduced in teaching materials, classroom interactions, and role modeling, largely due to a lack of teacher awareness and insufficient gender-sensitive pedagogy. Moreover, the dominance of female educators and the underrepresentation of male teachers in ECE contribute to limited gender role diversity for children. Cultural and social norms, particularly in traditional societies, further hinder the promotion of gender equality in early education. In contrast, several countries, particularly in Scandinavia and Canada, have successfully implemented inclusive gender pedagogies supported by policy and teacher training. This study emphasizes the urgent need for integrating gender equality into ECE curricula, enhancing teacher competence, and developing national policies that support equitable and inclusive early learning. The implications highlight the importance of transforming early childhood settings into spaces that actively deconstruct gender stereotypes and promote fairness and diversity from the outset of a child's educational journey.